Interpreting change on the Symbol Digit Modalities Test in people with relapsing multiple sclerosis using the reliable change methodology. (June 2022) - Weinstock, Zachary; Morrow, Sarah; Conway, Devon; Fuchs, Tom; Wojcik, Curtis; Unverdi, Mahmut; Zivadinov, Robert; Weinstock-Guttman, Bianca; Iverson, Grant L; Dwyer, Michael; Benedict, Ralph HB
Background: The Symbol Digit Modalities Test (SDMT) is increasingly utilized in clinical trials. A SDMT score change of 4 points is considered clinically important, based on association with employment anchors. Optimal thresholds for statistically reliable SDMT changes, accounting for test reliability and measurement error, are yet to be applied to individual cases. Objective: The aim of this study was to derive a statistically reliable marker of individual change on the SDMT. Methods: This prospective, case–control study enrolled 166 patients with multiple sclerosis (MS). SDMT scores at baseline, relapse, and 3-month follow-up were compared between relapsing and stable patient groups. Using data from the stable group and three previously published studies, candidate thresholds for reliable decline were calculated and validated against other tests and a clinically meaningful anchor—cognitive relapse. Results: Candidate thresholds for reliable decline at the 80% confidence level varied between 6 and 11 points. An SDMT change of 8 or more raw score points was deemed to offer the best balance of discriminatory power and external validity for estimating cognitive decline. Conclusion: This study illustrates the feasibility and usefulness of reliable change methodology for identifying statistically meaningful cognitive decline that could be implemented to identify change in individual patients, for both clinical management and clinical trial outcomes.